Research on Cultivating Entrepreneurship Ability of Graduate Students in the Field of Electronic Information - Hou Chengyu; Zhao Yaqin; Yin Zhendong; Liu Jinlong (SHS Web of Conferences, 2023)
This article aims to explore the generation process of graduate students' entrepreneurial ability in the field of electronic information from three aspects: entrepreneurial awareness, entrepreneurial skills, and entrepreneurial practice, in order to condense the key factors of graduate students' entrepreneurial ability. And then a mechanism and method are established for cultivating graduate students' entrepreneurial ability based on the analysis above.